UNDERCONFIDENCE INFLUENCES LONG TERM AND SHORT TERM DECISIONS IN CRYPTOCURRENCY INVESTMENT - Astiti, Ni Putu; Kepramareni, Putu (Faculty of Economic and Business, University of Pasundan, 2025)
According to prospect theory, investors evaluate gains and losses with certain tendencies. Investors assess losses and avoid risk in the domain of gains. When faced with choices involving potential losses or gains, loss aversion can lead to a tendency to avoid risks that could result in losses, even if the potential gains are substantial. The population in this study is cryptocurrency investors in Bali, whose number is unknown. The sample was determined based on the opinion that the number of indicators x 5-10, which is 150 samples. The sampling technique used is purposive sampling with the criterion that cryptocurrency investors have been investing for a minimum of 2 years. The data analysis technique used is SEM-PLS. Underconfidence does not affect cryptocurrency investment performance. Underconfidence positively affects Long Term Investment Decision and short term investment decision. Long Term Investment Decision and short term investment decision positively affect cryptocurrency investment performance.